PERSEPSI MAHASISWA NON-MUSLIM TERHADAP MODERASI BERAGAMA DI LINGKUNGAN PERGURUAN TINGGI UMUM DI ACEH - Kumalasari, Reni (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2025)
Several survey institutions show that Public Universities (PTU) are vulnerable to exposure to radicalism, at the same time other survey institutions place Aceh as the most intolerant province. To verify previous research, this research examines the opinions of non-Muslim students regarding the practice of religious moderation in campus environments, namely Teuku Umar University (UTU) Meulaboh and Syiah Kuala University (USK) Banda Aceh. This research aims to describe the perceptions of non-Muslim students regarding implementing religious moderation in the environments of the two campuses. This research is a qualitative study that explains students' perceptions of religious moderation which are described using the four religious moderation indicators of the Indonesian Ministry of Religion. The data in this research was collected using interview techniques, questionnaires, and documentation. The results of this research show that the two PTUs are committed to implementing the values ​​of Pancasila and the 1945 Constitution, respecting minority religions, not being exclusive, and having an accommodating attitude towards culture. Overall, the percentage of non-Muslim students' perception level regarding the implementation of religious moderation is 73.25%.